Educational efficacy of medical humanities in empathy of medical students and healthcare professionals: a systematic review and meta-analysis - Xin Zhang; Hui-fang Pang; Zhiguang Duan (BMC Medical Education, 2023)
Abstract Background Medical humanities education is an important part of medical education. The purpose of this study was to determine the effectiveness of medical humanities in improving empathy among medical students and healthcare professionals. Methods PubMed, Embase, EBSCO-ERIC, Web of Science were searched systematically for studies in the English language. The last retrieval date is May 1, 2023. Best Evidence Medical Education (BEME) Global Rating Scale and Kirkpatrick-based results were used to evaluate the quality of literature. In this study, a meta-analysis of continuous data was conducted. Results The pooled results by single-arm test meta-analysis showed a benefit with medical humanities programs in empathy (SMD 1.33; 95% CI 0.69–1.96). For single-arm trials of medical humanities program interventions of less than 4 months, 4 months to 12 months, and more than one year, the standardized mean differences(SMD) between post-test and pre-test were 1.74 (P < 0.05), 1.26 (P < 0.05), and 0.13 (P = 0.46), respectively. The results showed a significant difference in the effect of medical humanities programs on male and female empathy (SMD − 1.10; 95% CI -2.08 – -0.13). The SMDs for the study of course, the course combined reflective writing, and the course combined reflective writing and practice as intervention modalities for medical humanities programs were 1.15 (P < 0.05), 1.64 (P < 0.05), and 1.50 (P < 0.05), respectively. Conclusion Medical humanities programs as a whole can improve the empathy of medical students and health professionals. However, different intervention durations and different intervention methods produce different intervention effects.